Structural transect through Ellesmere Island (Canadian Arctic):superimposed Palaeozoic Ellesmerian and Cenozoic Eurekan deformation - Piepjohn, Karsten; Gosen, Werner Von (Figshare, 2017)
The 400 km long transect through Ellesmere Island is located perpendicular to the North American continental margin between the Arctic Ocean in the NNW and the Greenland–Canadian Shield in the SSE. It provides an insight into the structural architecture and tectonic history of the upper parts of the continental crust. The northernmost segment of the transect is dominated by the composite Pearya Terrane, which amalgamated with the Laurentian margin during the Late Devonian–Early Carboniferous Ellesmerian Orogeny. The Neoproterozoic to Devonian Franklinian Basin is exposed south of the terrane boundary and most probably overlies the crystalline basement of the Greenland–Canadian Shield. The structures along the transect in this area are dominated by kilometre-scale Ellesmerian folding of the Franklinian Basin deposits above a deepseated detachment, which is suggested to be located at the boundary between the basement of the Canadian Shield and the overlying >8 km thick Franklinian Basin. Following the development of the Late Mississippian–Palaeogene Sverdrup Basin, the complex Eurekan deformation reactivated Ellesmerian thrust faults and probably parts of the associated deep-seated detachment. In addition, large Eurekan strike-slip faults affected and displaced pre-Eocene deposits and tectonic structures, particularly in the northern part of the transect.